119 Circulating Plasma Nitrosothiols Levels Rise in Response to Prasugrel Loading in Patients with Coronary Artery Disease Undergoing Elective Percutaneous Coronary Intervention. (6th June 2015) - Thornhill, Laurence; Morris, Keith; James, Philip; Anderson, Richard
Abstract : Introduction: Clopidogrel and prasugrel are well established antiplatelet agents used for the treatment of acute coronary syndromes (ACS). Clopidogrel is known to improve endothelial function in patients with coronary artery disease but little is known about the more potent thienopyridine prasugrel. Both agents form S-nitrosothiols (RSNO) in vitro in the presence of background nitrite in an acidic environment, with prasugrel capable of producing the most. We aimed to investigate whether prasugrel could influence RSNO bio-synthesis in vivo by assessing the effect of acute (2 hrs) and chronic (28 days) prasugrel treatment on NO metabolite formation in patients. Methods: Blood samples were collected from 51 patients with known coronary artery disease undergoing percutaneous coronary intervention (PCI). 34 were sampled pre and 2 h post loading with prasugrel 60 mg and compared with 17 patients receiving prasugrel 10 mg for over 28 days. Established ozone-based chemiluminescence techniques were employed to measure the principal NO metabolites nitrite, nitrate, and nitrosothiol (RSNO) in blood samples. Platelet aggregation in the same samples was measured using Multiplate® multiple electrode aggregometry. Results: Plasma RSNO levels increased significantly (25.5 v 34.7 nmol/L; p = 0.0018), with plasma nitrite also increasing in parallel (239.9 v 268.1 nmol/L; p = 0.0048). Corresponding plasma nitrate levels decreased (40.6 v 38.2 µmol/L; p = 0.0059). Patients receiving chronic prasugrel maintained elevated RSNO and nitrite levels. Prasugrel induced RSNO in plasma was largely protein based (>58%), in keeping with the efficient transnitrosation potential of thienopyridine-SNO. Platelet aggregation was markedly inhibited by prasugrel in response to the agonists ADP (p = 0.0001) and TRAP (p = 0.0001) in both the acute and chronic setting. Conclusions: Prasugrel induces an acute rise in plasma RSNO and nitrite following a loading dose in patients with coronary artery disease which are then maintained with chronic prasugrel treatment. Given the potent antiplatelet effects of RSNO and the potential cardioprotective effects of nitrite, this offers a new and alternative mechanism of action that has the potential to be exploited in terms of future antiplatelet therapy.